Linear Transformations

T:R^3 ---> R^3 and U:R^3 ---> R^3

are defined by

x1 4x1-2x2+x3

T([x2])=[x1+3x2-x3 ]

x3 3x1+4x2-5x3

x1 x1+x3

U([x2])=[x1-3x2-x3]

x3 x1-x2

Determine the rule for UT

T:R^3 ---> R^3 and U:R^3 ---> R^3

are defined by

x1 4x1-2x2+x3

T([x2])=[x1+3x2-x3 ]

x3 3x1+4x2-5x3

x1 x1+x3

U([x2])=[x1-3x2-x3]

x3 x1-x2

Determine the rule for UT

### Recently Asked Questions

- A random sample of 15 monthly rents for two-bedroom apartments was selected from a certain city. The mean of this sample is $636. Assume the population

- Business management class question. The class is about change management and my question is " Identify the requisite skills a person needs to lead change."

- Please help me understand this question better. Thank you!